Pemodelan Ketergantungan antara Foreign Directed Investment (FDI) dengan Gross Domestic Product (GDP) Menggunakan Kopula - Agus Supandi; Wulan Anggraeni; Arief Nugroho Wibowo (LITERATUS, 2021)
The purpose of this study is to model the dependence of FDI and GDP. The method of this research is copula. The steps are stationary test, ARIMA model determination, heteroscedasticity test, data residue transformation, normality test, tau Kendal correlation coefficient test, calculation of Archimedean class parameter values, MSE calculation. From the series carried out, it was found that the clayton copula was selected in modeling the dependence of FDI and GDP.